Leaving-But Not Yet Left: A Rejection of the Perception „God‟s Waiting Room‟ in Favour of Humanistic Residential Aged Care (International Journal of Studies in Nursing, 2019)
Background: Healthcare systems worldwide will be increasingly challenged to meet the complex needs of aging populations. In particular, the operation of residential aged care facilities will require improved surveillance and monitoring to ensure that quality assurance systems are in place that support holistic and humane care of all aged care residents. Objectives: To undertake a selected literature search including a focus on Australian based case studies with the intention of a) developing a philosophical orientation towards improving awareness and understandings among policy makers and residential aged care workers to transform residential aged care into an environment that protects human rights b) drawing attention to how the adoption of an attitude that sees aged care recipients as having left while still living has the potential to create a minimalist approach to care and c) highlighting the need for emotionally intelligent leadership as a core component for establishing, facilitating and coordinating the delivery of quality assurance systems in residential aged care. Methodology: This is not a quantitative study but one essentially focused on offering a professional perspective on residential aged care resulting from a reading of selected literature and the combined existential experiences and understandings of both authors. The preceding approach provided the groundwork for presenting a case for honouring human rights in tune with the adoption of a substantive philosophy for the overall operation of residential age care facilities. Conclusion: While entry into residential aged care can be seen to represent the final chapter in an older person‟s life, there remains the ever-present mandate for formal caregivers to not stray from the moral obligations associated with „ethical caregiving‟.